2019
DOI: 10.3390/cells9010075
|View full text |Cite
|
Sign up to set email alerts
|

Precision Medicine in Neurodegenerative Diseases: Some Promising Tips Coming from the microRNAs’ World

Abstract: Novel insights in the development of a precision medicine approach for treating the neurodegenerative diseases (NDDs) are provided by emerging advances in the field of pharmacoepigenomics. In this context, microRNAs (miRNAs) have been extensively studied because of their implication in several disorders related to the central nervous system, as well as for their potential role as biomarkers of diagnosis, prognosis, and response to treatment. Recent studies in the field of neurodegeneration reported evidence th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 107 publications
(147 reference statements)
0
4
0
Order By: Relevance
“…In the last few years, circulating miRNAs have been proposed as potential diagnostic and prognostic biomarkers or even as therapeutic targets for various diseases, including CNS disorders like MS [ 6 , 17 , 72 , 73 ]. The let-7 family regulates many target mRNAs by participating in crucial processes for MS pathophysiology (neuronal homeostasis [ 17 , 24 , 25 ], inflammation [ 1 , 17 ] and miRNA metabolism [ 5 , 26 , 27 ], as in Figure 1 B,B’).…”
Section: Discussionmentioning
confidence: 99%
“…In the last few years, circulating miRNAs have been proposed as potential diagnostic and prognostic biomarkers or even as therapeutic targets for various diseases, including CNS disorders like MS [ 6 , 17 , 72 , 73 ]. The let-7 family regulates many target mRNAs by participating in crucial processes for MS pathophysiology (neuronal homeostasis [ 17 , 24 , 25 ], inflammation [ 1 , 17 ] and miRNA metabolism [ 5 , 26 , 27 ], as in Figure 1 B,B’).…”
Section: Discussionmentioning
confidence: 99%
“…The identification of miRNAs dysregulated in neurodegenerative diseases and construction of related animal models may thus aid in delineation of molecular mechanisms underlying their pathologic processes ( Juzwik et al, 2019 ). Moreover, exploitation of these molecular pathways via precision therapy strategies for neurodegenerative diseases is well underway ( Junn and Mouradian, 2012 ; Pereira et al, 2017 ; Nuzziello et al, 2019 ). While piRNAs have a well-established role in the protection of the germline genome, they also function in somatic cells including neurons ( Lee et al, 2011 ; Yan et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent progress related to microRNA (miRNA) pharmaco-epigenomics, defined as the use of drugs to treat epigenetic defects connected to a disease, offers new strategies for the development of more effective treatments [82]. The implication of miRNAs in several brain disorders has, indeed, been extensively studied and many authors reported evidence of drug response regulated by miRNA-mediated mechanisms.…”
Section: Neurodegenerative Diseasesmentioning
confidence: 99%